Application of Kano Model for Customer Satisfaction Analysis of Health Center Service Quality - Syakbani, Fajri Furqon; Rahmiati, Rahmiati (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
In the health service sector, especially community health centers, service quality is an important issue considering its function as a first-level health facility that serves the wider community. Where customer satisfaction is an important benchmark for assessing the extent to which the health services provided are able to meet the needs of the community. This study aims to analyze customer satisfaction with service quality attributes at the Tanjung Ampalu community health center based on the Kano model. This study is a quantitative study involving 317 respondents with a survey research data collection method. This study adopts research instruments from previous researchers from reputable journals which use dimensions of service quality using the Kano model. The results of this study reveal that the dimensions of tangibles, reliability, responsiveness, and assurance at the Tanjung Ampalu community health center are classified into the one-dimensional category, while the empathy dimension is classified into attractive. which indicates that each service quality attribute in this study is very important and crucial in increasing customer satisfaction.